Hubungan Kadar Interleukin-10 Serum dan Kadar Leukosit Darah Perifer pada Pasien Cedera Otak Berat Akibat Trauma - Suyanto, Edih; Prasetyo, Eko; Oley, Maximillian Ch. (UNIVERSITAS SAM RATULANGI, 2018)
Abstract: This study was aimed to prove that in severe traumatic brain injury (TBI) there was an elevation in serum IL-10 level as well as in peripheral blood leukocyte level, and a correlation between both of them. This was an analytical correlational study. All patients had IL-10 level above normal value (18 pg/ml). There were three patients with normal blood leukocyte level. The correlation between IL-10 and blood leukocyte level was tested by using simple linear regression analysis and Pearson correlation coefficient analysis which obtained r = 0.045 with a P of 0.426 (>0.05). These results indicated a positive relationship between IL-10 and leukocytes levels, but not statistically significant. Conclusion: Interleukin-10 was consistantly elevated following severe traumatic brain injury and was a better TBI biomarker than the peripheral leukocyte level.Keywords: IL-10, leukocytes, TBIAbstrak: Penelitian ini bertujuan untuk membuktikan bahwa pada cedera otak akibat trauma (COT) berat terdapat peningkatan kadar serum IL-10 dan kadar leukosit darah perifer serta korelasi antara keduanya. Jenis penelitian ini ialah analitik korelasional. Hasil penelitian mendapatkan 20 pasien dengan COT berat berusia 16-65 tahun. Semua pasien memperlihatkan kadar Il-10 di atas nilai normal (18 pg/ml). Terdapat 3 pasien dengan kadar leukosit dalam batas normal Hubungan antara IL-10 dan leukosit diuji dengan analisis regresi linier sederhana dan analisis koefisien korelasi Pearson dan mendapatkan r = 0,045 dengan P = 0,426. Hasil ini menunjukkan hubungan positif antara IL-10 dan leukosit, tetapi tidak bermakna secara statistik (P = 0,426 >0,05). Simpulan: IL-10 secara konsisten meningkat setelah COT dan sebagai biomarker COT yang lebih baik daripada leukosit perifer.Kata kunci: IL-10, leukosit, COT